Recent Developments in Microfinance - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 1998)
Our knowledge about microfinance in developing countries has been greatly enriched in recent years by the experience of numerous institutions. Different sound technologies and practices of financial services to all segments of the population have emerged; there is no single best practice or optimal approach that could be simply replicated. People and institutions have to find out what suits them best. Through trial and error, they gain the experience which may then be cast into lasting innovations. Five case studies are presented, each with its own lessons concerning viability, sustainability, and outreach: two from Indonesia, two from Nepal, and one from India. In addition, lessons are drawn from the recent financial crisis in Indonesia concerning the importance of a triad of framework conditions: prudential deregulation, macroeconomic stability, and adequate bank supervision. The data are largely based on the author?s field research and consultancy work.
Keywords: 330; Informeller Finanzsektor; Klein- und Mittelunternehmen; Finanzierung; Asien